A model of low-velocity impact damage of composite plates subjected to Compression-After-Impact (CAI) testing. (1st December 2017) - Rozylo, P.; Debski, H.; Kubiak, T.
Abstract: The paper presents a simplified model of damage of composite plates (SDM) subjected to low-velocity impact testing. The damage model assumes reduced thickness of laminate plies versus impact energy. The decrease in strength of the lay-up was measured by Compression-After-Impact (CAI) tests. The numerical analysis was performed on composite plates made of CFRP laminate subjected to uniform compression, with represented regions of damage caused by different impact energies. The numerical results show the behaviour of the laminate during compression, taking into account the damage process evaluated by a progressive damage criterion. The numerical analysis was performed using the ABAQUS® programme. The results were verified based on experimental findings reported in the literature and the numerical results of the tested composite plates subjected to CAI testing.